Mapping the Futures of Islamic Philanthropy: A Bibliometric Analysis of Global Trends and its Foresight Directions - Anggara, Fajar Surya Ari; Faradisi, Roghiebah Jadwa (ZISWAF ASFA, 2025)
Lack of literature integrating trend analysis with foresight to plan Islamic philanthropy's future and bibliometric analysis. How has worldwide Islamic philanthropy intellectuality changed?  What emerging trends and orientations may bibliometric analysis reveal? This study uses mixed approaches.  This study uses quantitative bibliometrics and qualitative content analysis to examine Islamic philanthropy's intellectual environment.  This study searches Scopus for "philanthropy", "Islamic philanthropy", "future studies", and "bibliometric" from 1985 to 2025.  VosViewer, Biblioshiny, PoP, and Google Trends will map intellectual landscapes, follow citation patterns, and visualise worldwide Islamic philanthropic trends.  Bibliometric measures like publication counts and citation metrics will measure this field's research impact and growth.  The results found include the phase of publication output and the development of future trends related to Islamic philanthropy. since the 1990s, early studies mostly concentrated on conventional practices and their religious-legal underpinnings.  With more focus on socio-economic consequences and community development, the field grew significantly between 2000 and 2010.  Particularly the Sustainable Development Goals (SDGs), the years 2010 to 2020 saw integration with world trends.  Developing SDGs practices, digital transformation with linked development like artificial intelligence, Big Data for Islamic Philanthropy will help 2025 and beyond. Artificial intelligence and massive data make decisions predictive.  Integrating Shariah compliance, sustainability, and inclusivity.  Digitally adaptable as fintech, blockchain, and IoT will also change Islamic social finance world in future.